Nesfatin-1 as a crucial mediator of glucose homeostasis in the reptile, Hemidactylus flaviviridis - Krittika Dotania; Mamta Tripathy; Umesh Rai (Scientific Reports)
Abstract Nesfatin-1 is a crucial regulator of energy homeostasis in mammals and fishes, however, its metabolic role remains completely unexplored in amphibians, reptiles, and birds. Therefore, present study elucidates role of nesfatin-1 in glucose homeostasis in wall lizard wherein fasting stimulated hepatic nucb2/nesfatin-1, glycogen phosphorylase (glyp), phosphoenolpyruvate carboxykinase (pepck), and fructose 1,6-bisphosphatase (fbp), while feeding upregulated pancreatic nucb2/nesfatin-1 and insulin, suggesting towards tissue-specific dual role of nesfatin-1 in glucoregulation. The glycogenolytic/gluconeogenic role of nesfatin-1 was further confirmed by an increase in media glucose levels along with heightened hepatic pepck and fbp expression and concomitant decline in liver glycogen content in nesfatin-1-treated liver of wall lizard. Moreover, treatment with nesfatin-1 stimulated insulin expression in pancreas while insulin downregulated pancreatic nucb2/nesfatin-1. Further, prolonged fasting induced elevated nucb2/nesfatin-1, and lipolytic markers, adipose triglyceride lipase (atgl) and monoglyceride lipase (mgl) in adipose tissue implicate nesfatin-1 in lipolysis which is substantiated by nesfatin-1-mediated direct upregulation of atgl and mgl. Our study provides the first comprehensive overview of tissue-dependent role of nesfatin-1 in regulating energy homeostasis in a reptile.